단경 직립 내도복 다수성 땅콩 ‘일평’ - 배석복(Suk-Bok Pae); 황정동(Chung-Dong Hwang); 이명희(Myung-Hee Lee); 하태정(Tae-Joung Ha); 박장환(Chang-Hwan Park); 정영근(Young-Keun Cheong); 박금룡(Keum-Yong Park); 백인(In-Yeol Baek) (Korean journal of breeding, 2013)
간식용 대립 땅콩의 선호도가 높음에 따라 대립 양질 다수성 신품종 육성을 위하여 단경 박피 다수성인 ‘팔광’과 직립다수성 ‘유데라카’를 인공교배하여 ‘일평’을 육성하였다. ‘일평’은 버지니아 초형으로 개화기가 빠르고 지상부 생장습성은 단경 다분지성이다. ‘일평’은 ‘대광땅콩’에 비해 성숙협수,협실비율, 100협립수 등 양호한 등숙특성을 보이며 100립중이 85 g인 대립품종이다. ‘일평’의 도복은 매우 강한 특성을나타내며 흑반병, 그물무늬병에 비교적 강하고 낙엽율도 낮아 생육후기까지 녹엽 유지에 유리하였다. ‘일평’은 단백질이27.6%, 기름함량이 49.5%이고 지방산은 올레산과 리놀산이비슷한 비율로 나타났다. ‘일평’을 3년간 지역적응시험 결과‘대광땅콩’에 비하여 전국평균 4.47 ton로서 8% 증수되었다.‘일평’은 경장이 짧고 병해에도 강한 편이나 충분한 성숙을위하여 강원도와 산간 고냉지를 제외한 지역에서 적응성이높은 품종이다. A new peanut variety ‘Ilpyeong’ ( Arachis hypogaea ssp. hypogaea L.) was developed at the Department of Functional Crop, NICS, in Milyang in 2009. This cultivar was developed from a cross between the high-yielding cultivar ‘Palkwang’, and the high quality cultivar ‘Yudelaka’. ‘Ilpyeong’ which is Virginia plant type has 20 branch numbers per plant with long ellipse-shaped large kernel. Each pod has two grains with brown testa and 100 seed weight was 85 g in the regional yield trials (RYT). Seed quality showed 49.5% of crude oil and 27.6% of protein content. This variety also showed more resistance to late leaf spot and web blotch compared with check one. Especially it has resistance to lodging until harvesting owing to short stem and erect plant type. In the regional yield trials ‘Ilpyeong’ was outyielded than the check variety by 8% with 4.47 MT/ha for grain.